Reviewing high-level control techniques on robot-assisted upper-limb rehabilitation. (17th December 2018) - Miao, Qing; Zhang, Mingming; Cao, Jinghui; Xie, Sheng Q.
ABSTRACT: This paper presents a comprehensive review of high-level control techniques for upper-limb robotic training. It aims to compare and discuss the potentials of these different control algorithms, and specify future research direction. Included studies mainly come from selected papers in four review articles. To make selected studies complete and comprehensive, especially some recently-developed upper-limb robotic devices, a search was further conducted in IEEE Xplore, Google Scholar, Scopus and Web of Science using keywords ('upper limb*' or 'upper body*') and ('rehabilitation*' or 'treatment*') and ('robot*' or 'device*' or 'exoskeleton*'). The search is limited to English-language articles published between January 2013 and December 2017. Valuable references in related publications were also screened. Comparative analysis shows that high-level interaction control strategies can be implemented in a range of methods, mainly including impedance/admittance based strategies, adaptive control techniques, and physiological signal control. Even though the potentials of existing interactive control strategies have been demonstrated, it is hard to identify the one leading to maximum encouragement from human users. However, it is reasonable to suggest that future studies should combine different control strategies to be application specific, and deliver appropriate robotic assistance based on physical disability levels of human users. GRAPHICAL ABSTRACT: